Concentration-effect relationship of levodopa in patients with Parkinson's disease after oral administration of an immediate release and a controlled release formulation. - Harder, Sebastian; Baas, Horst; Bergemann, Niels; Demisch, L.; Rietbrock, S. (British journal of clinical pharmacology, 1995)
1. The relationship between plasma concentration of levodopa and motor- response was investigated in 12 patients with Parkinson's disease who showed marked response fluctuations, after a single oral dose of an immediate release (IR) formulation (100 mg levodopa/25 mg genserazide) and a controlled release (CR) formulation (300 mg levodopa/75 mg benserazide), using a double-blind, randomized, cross-over design. 2. The sum score of the Columbia University Rating Scale (CURS sigma) was used for pharmacodynamic assessment. A sigmoidal Emax-model was fitted to the data using a semiparametric pharmacokinetic/dynamic approach. 3. The dose-corrected AUC of levodopa after the IR-formulation was 27.5 (+/- 9.1 s.d.) ng ml-1 h per mg and 23.2 (+/- 4.6 s.d.) ng ml-1 h per mg after the CR-formulation. Cmax was 1714 (+/- 1027 s.d.) ng ml-1 after the IR-formulation and 1494 (+/- 383 s.d.) ng ml-1 after the CR- formulation. 4. With both preparations, the maximal response to levodopa (Emax) was a decrease in the CURS sigma rating of about 27 scores. Estimates of the EC50 of levodopa were 495 (+/- 144 s.d.) ng ml- 1 (IR) and 1024 (+/- 502 s.d.) ng ml-1 (CR), respectively (95%-CI: 1.51- 2.66, point estimator 1.95). The mean duration of the motor response was 1.9 (+/- 0.5 s.d.) h (IR) and 2.8 (+/- 0.7 s.d.) h (CR), respectively (95%-CI: 1.12-2.04, point estimator 1.53).(ABSTRACT TRUNCATED AT 250 WORDS)
Gesehen am 14.12.2020